KAJIAN KETERSEDIAAN LAHAN DITINJAU DARI RENCANA STRATEGIS PENGEMBANGAN KAMPUS BERKELANJUTAN (Studi Kasus di Beberapa Lokasi Kampus FKIP UNS) - Sukatiman, Sukatiman (Universitas Muhammadiyah Surakarta, 2015)
The research purposed was mapping campuses situations toward to sustainable strategic plan. Kind of research is qualitative descriptive focused on specific targets. Its comprises of exsisting condition in 3 location campuses, those were PTK Pabelan campus, PGSD campus, and FKIP UNS Kentingan campus. The research showed that : 1) environment condition of three (3) location campuses had sustainable infrastructure, available of reforestasion, and cozy environment. 2) PTK Pabelan and PGSD Laweyan campuses had available open space suitable with regulation of Public Works. 3) FKIP Kentingan campus was over land used.